1995
DOI: 10.1002/acp.2350090302
|View full text |Cite
|
Sign up to set email alerts
|

False memories of childhood experiences

Abstract: We conducted two experiments to investigate if college students would create false memories of childhood experiences in response to misleading information and repeated interviews. In both experiments we contacted parents to obtain information about events that happened to the students during childhood. In a series of interviews we asked the students to recall the parentreported events and one experimenter-created false event. In the second experiment we varied the age at which we claimed the false event occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
252
5
4

Year Published

1995
1995
2007
2007

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 419 publications
(281 citation statements)
references
References 29 publications
(39 reference statements)
13
252
5
4
Order By: Relevance
“…Thus, we hypothesized that the provision of self-relevant information may elevate false memory rates. This view is supported by Hyman, Husband, and Billings's (1995) finding that participants whose imagery included self-knowledge were more likely to endorse false events as true. Hence, it may have been the unconstrained nature of narratives, differences in self-relevant information, or both that resulted in differences between narratives and photographs in Garry and Wade's study.…”
Section: Materials and Measuressupporting
confidence: 75%
“…Thus, we hypothesized that the provision of self-relevant information may elevate false memory rates. This view is supported by Hyman, Husband, and Billings's (1995) finding that participants whose imagery included self-knowledge were more likely to endorse false events as true. Hence, it may have been the unconstrained nature of narratives, differences in self-relevant information, or both that resulted in differences between narratives and photographs in Garry and Wade's study.…”
Section: Materials and Measuressupporting
confidence: 75%
“…Indeed, false remembering may arise from repeated attempts at retrieval, as shown in Experiment 2 and elsewhere (e.g., Ceci, Huffman, Smith, & Loftus, 1994;Hyman, Husband, & Billings, 1995;Roediger et al, 1993). Retrieval processes may contribute significantly to the false recall and false recognition phenomena we have observed.…”
Section: Explanations Of False Recall and False Recognitionmentioning
confidence: 65%
“…Because narratives allow and even demand that subjects generate their own details, narratives should give subjects freedom to generate their own images, incorporate personal knowledge, and require deeper processing. By contrast, photographs impose more constraints on imagination because they depict specific details, people, and settings (see also Hyman, Husband, & Billings, 1995, who showed that subjects who incorporated self-knowledge into their imagery were more likely to develop false memories). Taken together, research suggests that narratives should establish more familiarity than should photos and make subjects more likely to falsely remember events.…”
mentioning
confidence: 99%